'I felt so removed from student teaching': shared voices of preservice student teachers regarding the edTPA and student teaching. Issue 2 (3rd April 2021) - Shin, Minsun
ABSTRACT: Guided by an inquiry as stance approach, this study aimed to explore the perspectives of early childhood and elementary pre-service student teachers on the impact of the edTPA (Teacher Performance Assessment) on their student teaching experiences. The analysis of an online open-ended questionnaire revealed that the claims made by the edTPA supports were paradoxical. Our participants shared the unforeseen effects of the edTPA on their student teaching experiences, such as the [non-]educative, [un]authentic, and [un]professional side of the edTPA. The findings of this study urge teacher educators, policy makers, and administrators to rethink and re-examine the edTPA requirement in the field to provide truly professional and educative experiences for all young children, student teachers, Cooperating Teachers (CT), staff, and the community.